Farm credit programs in Western Nigeria: a problem in administration and organization design - Ijose, Abiose (Ohio Ohaio State University, 1969)
The study sets out to explain the effectiveness and viability of a farm credit institution through the design of a management system
Dissertation presented in partial fulfilment of the requirements for the degree Doctor of Philosophy in the graduate school of the Ohio State University
Includes bibliographical references
osc 20/08/2021
Arch
Keywords: Agricultural Credit; Farm management; Nigeria